Pediatric blunt abdominal trauma with horizontal duodenal injury in school baseball: A case report. Issue 2 (15th January 2021) - Tokumaru, Teppei; Eifuku, Ryozo; Sai, Kenichi; Kurata, Hideaki; Hata, Michiaki; Tomioka, Joji
Abstract: Rationale: Pediatric sports injuries, including those from baseball, most often are musculoskeletal injuries and rarely include blunt abdominal injuries. Duodenal injury is rare and often associated with other organ injuries. Because it has a relatively high mortality, early recognition and timely treatment are needed. Here, we report a case of successful treatment of a pediatric patient with duodenal injury incurred in the context of school baseball. Patient concerns: A 13-year-old boy suffered blunt abdominal trauma and a right-hand injury caused by beating his abdomen strongly with his own right knuckle after he performed a diving catch during a baseball game. On the following day, the abdominal pain had worsened. Diagnoses: Computed tomography led to a suspicion of injury to the horizontal part of the duodenum. Interventions: The duodenal injuries were repaired by simple closure. On the 10th post-operative day, an abscess formed in the retroperitoneal cavity because of an occult pancreatic injury. Ultrasound-guided percutaneous drainage of the cavity was performed. Outcomes: The post-operative course of the abscess drainage was uneventful. The patient was discharged from our hospital on day 72 after admission and was in good health at the 9-month follow-up. Lessons: Regardless of the type of injury, we must assess the life-threatening conditions that can be expected based on the mechanism of the injury. In duodenal injuries, it is critical to perform surgical procedures and post-operative management based on the assumption of injuries to other organs.